Teologi Rasional Muhammad Abduh sebagai Landasan Filosofis Pembaruan Pendidikan Islam - Muhammad Redha; Zubaidah Zubaidah (LaKaspia, 2025)
This article examines the rational theology of Muhammad Abduh (1849-1905) as a philosophical foundation for the reform of Islamic education. As a leading figure in the modern Islamic reform movement, Abduh’s influence extended beyond Egypt to the wider Muslim world, including Indonesia. This study aims to analyze the central role of reason (‘aql) in Abduh’s theological and philosophical system and its implications for the reform of Islamic thought, education, and law. Departing from his critique of the stagnation of the Muslim community characterized by intellectual rigidity (jumud), blind imitation (taqlid), and uncritical adherence to tradition Abduh asserted that Islam is inherently compatible with sound reason and rationality. Using a qualitative library research method, based on primary sources such as Risālat al-Tawḥīd and relevant secondary literature, this study finds that Abduh positions reason as the main epistemological pillar for understanding moral and theological obligations, including knowledge of God, His attributes, the hereafter, and ethical responsibilities. Revelation functions as a confirmation and completion of reason, rather than as its opposite. Furthermore, Abduh strongly rejects fatalism (Jabariyyah) and affirms human free will (Qadariyyah) through the principles of ikhtiar and moral responsibility. These findings demonstrate that Muhammad Abduh’s rational theology not only represents a theological reform but also constitutes a philosophical foundation for a modern Islamic educational paradigm that is rational, critical, and transformative